Progress in oncology biosimilars till 2020: Scrutinizing comparative studies of biosimilar monoclonal antibodies. (July 2021) - Safdar, Aqsa; Butt, Muhammad Hammad; Ahmad, Abrar; Zaman, Muhammad
Stupendous elevation in the healthcare costs has followed with the inception of the current unconventional options of treatment available for cancer patients. There is a dire need of innovative financing approaches to lessen the financial load on healthcare system. Biosimilars are biological drugs consisting of an active ingredient from a reference biological drug that has a great potential of relieving financial load. Strict requirements from regulatory point of view are required as biosimilars are exceedingly similar to but not identical to the reference product. This provides with a certainty that no consequential differences from clinical point of view as compared to the respective biologics exists with regards to efficacy, safety and purity. Safety and effectiveness of biosimilars have been disclosed since more than 10 years of affirmations. However, there is a need to educate the healthcare professionals to abolish potential misconceptions and coalesce biosimilars into regular clinical practice. The present review focuses on providing an overview of regulatory aspects and requirements for biosimilars, the main challenges in the selection and development of biosimilars and the economic impact and financial savings observed in recent studies carried out in different parts of the world. In addition, we have discussed the different successful comparative studies which have been done in different parts of the world to depict the biosimilarity for monoclonal antibodies such as bevacizumab, trastuzumab and rituximab.